2003
DOI: 10.1074/jbc.m210574200
|View full text |Cite
|
Sign up to set email alerts
|

Biglycan, a Nitric Oxide-regulated Gene, Affects Adhesion, Growth, and Survival of Mesangial Cells

Abstract: During glomerular inflammation mesangial cells are the major source and target of nitric oxide that profoundly influences proliferation, adhesion, and death of mesangial cells. The effect of nitric oxide on the mRNA expression pattern of cultured rat mesangial cells was therefore investigated by RNA-arbitrarily-primed polymerase chain reaction. Employing this approach, biglycan expression turned out to be down-regulated timeand dose-dependently either by interleukin-1␤-stimulated endogenous nitric oxide produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 56 publications
4
59
0
1
Order By: Relevance
“…The observation that biglycan (BGN) is also a target of exogenous or endogenous NO in human MCs is consistent with studies by (Schaefer et al, 2003), who reported that BGN is an NO-regulated gene in rat MCs both in vitro and in vivo and that it is involved in the adhesion, proliferation and survival of MCs. Biglycan is a member of small, leucine-rich repeat glycoproteins/proteoglycans (SLRPs), which are thought to play a role as organizers of ECM (Hocking et al, 1998).…”
Section: Bereitgestellt Von | Universitaetsbibliothek Der Lmu Muenchensupporting
confidence: 75%
See 1 more Smart Citation
“…The observation that biglycan (BGN) is also a target of exogenous or endogenous NO in human MCs is consistent with studies by (Schaefer et al, 2003), who reported that BGN is an NO-regulated gene in rat MCs both in vitro and in vivo and that it is involved in the adhesion, proliferation and survival of MCs. Biglycan is a member of small, leucine-rich repeat glycoproteins/proteoglycans (SLRPs), which are thought to play a role as organizers of ECM (Hocking et al, 1998).…”
Section: Bereitgestellt Von | Universitaetsbibliothek Der Lmu Muenchensupporting
confidence: 75%
“…Overexpression of BGN is found in advanced stages of glomerulosclerosis (Davies, 1995). BGN is capable of inhibiting the proliferation of MCs induced by PDGF-B, a major mitogenic growth factor frequently involved in glomerular disease (Blom et al, 2001;Schaefer et al, 2003).…”
Section: Bereitgestellt Von | Universitaetsbibliothek Der Lmu Muenchenmentioning
confidence: 99%
“…21,22 The differences between our study and previous studies could simply be due to differences in the antibody affinity or to the examination of different stages of renal disease. In addition, the functional role or roles of biglycan are unclear; roles have been proposed in the maintenance of the glomerular charge barrier, 48,49 in the regulation of mesangial cell growth and survival, 50 in the regulation of TGF-␤ activity, 51 in the regulation of inflammation via activation of Toll-like receptors, 52 in the regulation of the assembly of connective tissues, 53 and in the structural composition of fibrosis, 22 among others. Both biglycan and decorin can bind TGF-␤, leading to its sequestration and neutralization of activity.…”
Section: Discussionmentioning
confidence: 99%
“…43 Interaction of biglycan with other RTKs involved in decorin signaling has not been investigated up to now. Even though there is some evidence for the involvement of biglycan in inflammation, [44][45][46] only recently biglycan-mediated signal transduction has been described in macrophages. 14 Biglycan is abundant in the ECM of various organs.…”
Section: Biglycan: a Signaling Molecule And Endogenousmentioning
confidence: 99%